2018
DOI: 10.4018/jgim.2018100107
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Acceptance and Use of ICT Innovations by Agribusinesses

Abstract: This article describes how because of the rapid expansion of digital and online ‘bizscapes,' and ‘bizapps' resulting in small and medium-scale agribusinesses adopting and using online entrepreneurial technology innovations, information and communication technology has great potential to enhance the performance and efficiency of agribusinesses. The urge to understand factors that affect information technology innovations adoption and use by small and medium agribusinesses prompted this study, which involves the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Additionally, the study findings suggest that the expectancies of technology need to be enhanced to garner better understanding of the intention formation of technology adoption and further use of the technology. The expectancies postulated by UTAUT can be applied to examine the use of technology (i.e., CAPs) [71].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study findings suggest that the expectancies of technology need to be enhanced to garner better understanding of the intention formation of technology adoption and further use of the technology. The expectancies postulated by UTAUT can be applied to examine the use of technology (i.e., CAPs) [71].…”
Section: Discussionmentioning
confidence: 99%
“…The UTAUT2 model and its precursor, the UTAUT model, have been used to study adoption of a number of innovations, including MP services by Korean consumers (Lee et al , 2019), online entrepreneurial information and communication technology by agribusinesses (Ibrahim et al , 2018), e-learning adoption by academicians (Uğur and Turan, 2018), e-banking services by Chinese consumers (Wang et al , 2017), mobile wallets by Indian consumers (Singh et al , 2017), adoption of internet banking by Jordanian consumers (Alalwan et al , 2018) and remote MP in the UK (Slade et al , 2015b; Slade et al , 2014). Given the use of UTAUT and UTAUT2 as a framework to understand mobile MP adoption in other cultures (Slade et al , 2015a, 2015b; Baabdullah et al , 2019; Hussain et al , 2019; Lee et al , 2019), the UTAUT2 framework was adopted to assess MP acceptance among Colombian consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Similar constructs exist in five additional models and theories, including perceived usefulness in the Technology Acceptance Model, extrinsic motivation in the Motivational Model, job-fit in the Model of PC Utilization, relative advantage in the Diffusion of Innovation, and outcome expectancy in the Social Cognitive Theory. Performance expectancy was found as the strongest predictor of an individual's intention to use new technologies in an organizational context, and prior studies in the field found that there was a positive relationship between performance expectancy and continuance intention by (Raza et al, 2017;Maruping et al, 2017;Ibrahim et al, 2018;Kit et al, 2021). It is significantly influence behavioural intention to use big data analytic in companies (Cabrera-Sanchez & Villarejo-Ramos, 2020) ; influenced the use of e-commerce (Shahzad et al, 2020) ; influencing usage of public electronic procurement among Malaysian's SMEs (Kit et al, 2021) ; a significant predictor of the behavioural adoption of e-commerce (Mensah et al, 2021) ; a significant predictor of cloud computing adoption (Khayer et al, 2021) and a positive effect on the continuance intention of accountants to use Accounting Information System (Lutfi, 2022).…”
Section: Performance Expectancymentioning
confidence: 88%
“…To review the previous study, the author focused on the studies which applied UTAUT and SMEs. UTAUT has been applied by many researchers to study DWP adoption in SMEs such as accounting information system (Lutfi, 2022); cloud computing technology (Khayer et al, 2021); e-commerce (Shahzad et al, 2020) & (Sombultawee, 2020); electronic procurement Kit et al (2021); Soong et al (2020) digital advertising (Reyes-Mercado & Barajas-Portas, 2020) ; enterprise system (Awa & Ukoha, 2020); social media (Alhaimer, 2019); smart manufacturing technology (Chei et al, 2019); big data (Silva et al, 2019); Internet technology adoption (Dasgupta & Gupta, 2019) and business application (Ibrahim et al, 2018) The environmental factor was a positive predictor of the performance expectancy of electronic commerce (EC) among SMEs, it does not, however, encourage the adoption of EC. The knowledge factor is a significant determinant of the adoption of EC among SMEs.…”
Section: Definition and Conceptualizations Of Digital Workplacementioning
confidence: 99%